Investigating the Effectiveness of Cognitive-Behavioral Approach Couple Therapy on the Internalized Behavioral Problems of Children Aged 10 - 15 with Autism Spectrum Disorder - Kheirkhah, Homa; Gholamali Lavasani, Masoud; Afrooz, Golamali (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The current research aimed to investigate the effectiveness of implementing a cognitive-behavioral approach-based couple therapy program on parents and the reduction of internalized behavioral problems in students with autism spectrum disorder.Method: The present research design was quasi-experimental, utilizing a pre-test, post-test, and follow-up design with a control group. The population consisted of all parents with autistic sons aged 10 to 15 years in the city of Mashhad, from which 56 eligible parents (couples) were selected through convenience sampling and placed into two groups: experimental and control (each group comprising 28 parents). The experimental group underwent twelve 90-minute sessions of couple therapy with a cognitive-behavioral approach by Dattilio (2005; 2009), while the control group was on a waitlist. Both groups responded to the Achenbach Child Behavior Checklist at three stages. Data were analyzed using repeated measures analysis of variance with SPSS.22 software.Findings: The results indicated that the implementation of couple therapy with a cognitive-behavioral approach on parents significantly reduced the internalized behavioral problems (F=29.48, P